2021
DOI: 10.3389/fpsyg.2021.750803
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making Support for People With Alzheimer’s Disease: A Narrative Review

Abstract: The proportion of people with dementia has been increasing yearly, and the decision-making capacity of these people has become a major concern in fields such as the financial industry and in medical settings. In this narrative review, we discuss decision-making in people with Alzheimer’s disease (AD), and we propose the support for decision-making in people with AD, especially financial and medical decision-making. We summarize several hypotheses and theories on the decision-making capacity of people with AD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…A decrease in grooming numbers without any recovery in central and peripheral time may not be a reliable indicator of animal stress and anxiety 53,54 . People with dementia have di culties performing a variety of decision-making in daily living 55 . Brain regions associated with decision-making are frontal, temporal, and parietal regions and these areas vulnerable to age-related change 56 .…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in grooming numbers without any recovery in central and peripheral time may not be a reliable indicator of animal stress and anxiety 53,54 . People with dementia have di culties performing a variety of decision-making in daily living 55 . Brain regions associated with decision-making are frontal, temporal, and parietal regions and these areas vulnerable to age-related change 56 .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first review that attempts to analyze findings of previous studies on the causes of reduced decision-making ability in patients with AD from the perspective of interoception. While our previous study investigated the reasons for reduced decision-making ability in patients with AD (Sun et al, 2021 ), the role of interoception was not taken into account. By analyzing the theoretical background and brain neural underpinnings involved in interoception and decision-making, we found that these brain areas are often simultaneously affected by AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…We discussed the decrease in the decision-making ability of patients with AD in our previous article (Sun et al, 2021 ). We found their decision-making ability was influenced by both internal and external factors.…”
Section: Interoception and Decision-making In Admentioning
confidence: 99%
“…Moreover, with the prevalence of neurodegenerative diseases such as Alzheimer's and Parkinson's on the rise, there is a pressing need to delve deeper into how these conditions intersect with decision-making abilities [62,63]. Exploring the neural mechanisms underlying decision making in individuals affected by such diseases can provide invaluable insights into their cognitive decline and potential interventions.…”
Section: Future Perspectivesmentioning
confidence: 99%